Prediction of shear strength of reinforced concrete squat shear walls-comparative studies - Rao, G. Appa; Sivaguru, V. (Journal of Structural Engineering, 2024)
The prediction of shear strength of RC walls by various empirical, semi-empirical and code equations is highly deviating.The accuracy of such predictions is a great concern for the designers. Such deviation in the prediction needs to beaddressed. Several predicting equations proposed and reported prominently in various sources have been assessedthrough statistically based 333 selective experimental data points. The box and whisker plot has been developed forthe scatter of the ratio of predicted-to-measured ultimate shear strength for all the predictive equations. The deviationof the predicted shear strength of RC walls as per the existing equations has been inferred. The prediction of theshear strength of RC shear wall by very few equations are in close proximity with the statistical experimental data.Though several factors influence the shear strength of RC walls, the role of vertical and horizontal reinforcement, axialload, and boundary elements is still debatable. The selective main factors influencing the shear strength of RC wallshave been emphasised. The refined predictive model has been described from the assessment of the data in terms ofinfluencing factors on the shear strength and behaviour of RC shear wall. The best predictions have been validatedwith the popularly accepted experimental results.